Case report: Severe, refractory hypoglycemia in a 9-year-old Brittany Spaniel with renal nephroblastoma - Simons, Paula; Lyons, Bridget; Bentley, Adrienne; Mazzaferro, Elisa; Thalheim, Lindsay; Finotello, Riccardo; Ressel, Lorenzo (Frontiers in Veterinary Science, 2023)
A 9-year-old female spayed Brittany Spaniel presented for weakness and stumbling, and was diagnosed with severe hypoglycemia. An insulin to glucose ratio was not consistent with insulinoma as a cause for hypoglycemia. Diagnostic imaging (abdominal ultrasound and computed tomography) revealed a large left renal mass and concern for a metastatic lesion in the right kidney. Glucagon therapy was initiated, but hypoglycemia was refractory to therapy. A left nephrectomy was performed and hypoglycemia subsequently resolved. Histopathology of the mass was consistent with nephroblastoma and immunohistochemistry for anti Insulin-like Growth Factor-2 (IGF-2) antibody revealed positive staining in over 50% of the neoplastic cells. Chemotherapeutic treatment was initiated with a combined protocol of vincristine and doxorubicin. This is the first case report documenting the treatment of severe, refractory non-islet cell tumor-induced hypoglycemia in a dog, suspected to be secondary to an IGF-2 secreting nephroblastoma.